The impact of audit quality in rights offerings. (28th December 2018) - Balachandran, Balasingham; Faff, Robert; Nguyen, Lily H. G.; Puwanenthiren, Premkanth
Abstract: Using audit quality as our core focus, we take a fresh look at the tradability and standby status in rights offerings, and the market reaction during the subscription period in the US market. We find that firms with high audit quality are more likely to choose tradable or full standby rights issues. We also find that the subscription period price reaction is positively related to audit quality and negatively related to issue price discount. These results demonstrate an important role played by the choice of auditors in the design of rights offerings, particularly in mitigating the negative price reaction during the subscription period.